Counterfeit activities: enforcing the law of border measure / Jaffiqa Mohd Nasir …[et al.] - Mohd Nasir, Jaffiqa; Ishak, Ruhaizan; Mohd Soffian Lee, Umi Khairunnisa; Abdul Nasir, Umi Idayu (2013)
In the past two decades, the issue of counterfeiting has risen vividly. Therefore, governments around the world are starting to pay attention to the issue. Most counterfeit goods are luxury goods bearing a well-known trademark. The international standards of Custom control were established under Section 4 (Article 51-Article 61) of the enforcement of Intellectual Property rights "Special Requirement Related to Border Measures" of TRIPs Agreement, as one of the mosl important enforcement provisions for combating counterfeiting. Nationally, Section 70(D) and 70(0) of the Malaysian Trademark Act 1976 are somehow similar to section 89(2) of the United Kingdom Trademark Act 1994 the enforcement in the United Kingdom has been effectively enforced as compared to Malaysia. Sadly, these provisions have not been effectively enforced in Malaysia unlike United Kingdom. Therefore, this research will highlight on the existence of the law in Malaysia that govern the admission of counterfeit products and its ineffectiveness. This was done by comparing with United Kingdom.